Laryngeal sarcomatoid carcinoma: a case report and literature review on potential molecular targets for therapeutic opportunities - Fan, Jie; Chen, Lun; Li, Chen-Hui; Xiao, Zhong-Yong; Zhou, Shui-Hong (Frontiers in Oncology, 2025)
Laryngeal sarcomatoid carcinoma (LSC) is a rare variant of laryngeal malignancies characterized by an aggressive nature and poor prognosis, predominantly affecting older males. Although early diagnosis may facilitate organ preservation through adjuvant chemotherapy and radiation therapy, advanced stages of the disease, as classified by the TNM system, necessitate a deeper understanding of molecular interactions. This understanding could potentially yield improved molecularly targeted therapeutic opportunities and early diagnosis that likely support the treatment benefits in the LSC. Therefore, this study aims to identify possible molecular targets in LSC to better inform therapeutic options and prognostic markers for obtaining treatment benefits, alongside presenting a case study of a patient with LSC who was admitted to our department.